The current gold standard breast volumetry technique seems to overestimate fat graft volume retention in the breast: A validation study. Issue 8 (August 2019) - Herly, Mikkel; Müller, Felix Christoph; Ørholt, Mathias; Hansen, Joachim; Sværke, Sophie; Hemmingsen, Mathilde N.; Rasmussen, Bo S.; Elberg, Jens J.; Drzewiecki, Krzysztof T.; Vester-Glowinski, Peter V.
Summary: Background: MRI is generally considered as the gold standard for measuring breast volume because of its high accuracy of the modality. Many techniques used to measure total breast volume have been validated, but none of these techniques have been validated for their ability to measure the volume retention of fat grafts in the breast. In this study, the authors investigated the accuracy of the most common MRI technique used to measure fat graft retention in the breast by measuring the volume changes after breast augmentation. Methods: Patients undergoing breast augmentation with either breast implants or fat grafting underwent MRI scans before and after surgery. Blinded observers measured the change in breast volume from the MRI scans. The difference between the measured change in breast volume and the volume of the breast augmentation was used to determine the accuracy of the MRI technique. Results: Twenty-eight patients with a total of 56 breasts were included. In total, 168 measurements of change in breast volume were performed by the observers. The MRI measurements of change in breast volume overestimated the true volumes of the breast augmentations by an average of 50.8%, and only 8 of the 168 individual measurements had measurement errors below 50 mL. Conclusion: The MRI technique, which is considered as the gold standard for the quantification of fat graft volume retention, was associated with a significant measurement error. These findings have potential implications for the interpretation of previously published results of studies based on this technique.